The D&P Shapley value: a weighted extension - Yu-Hsien, Liao (Ukrains’kyi Matematychnyi Zhurnal, 2016)
First, we propose a weighted extension of the D&P Shapley value and then study several equivalences among the potentializability and some properties. On the basis of these equivalences and consistency, two axiomatizations are also proposed.